√x^2+y^2/√(x-3)^2+y^2=1/2 如何化简成曲线方程:x^2+y^2+2x-3=0(√是根号)√x^2+y^2/√(x-3)^2+y^2=1/2 如何化简成曲线方程:x^2+y^2+2x-3=0
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 22:58:00
√x^2+y^2/√(x-3)^2+y^2=1/2如何化简成曲线方程:x^2+y^2+2x-3=0(√是根号)√x^2+y^2/√(x-3)^2+y^2=1/2如何化简成曲线方程:x^2+y^2+2x
√x^2+y^2/√(x-3)^2+y^2=1/2 如何化简成曲线方程:x^2+y^2+2x-3=0(√是根号)√x^2+y^2/√(x-3)^2+y^2=1/2 如何化简成曲线方程:x^2+y^2+2x-3=0
√x^2+y^2/√(x-3)^2+y^2=1/2 如何化简成曲线方程:x^2+y^2+2x-3=0
(√是根号)
√x^2+y^2/√(x-3)^2+y^2=1/2 如何化简成曲线方程:x^2+y^2+2x-3=0
√x^2+y^2/√(x-3)^2+y^2=1/2 如何化简成曲线方程:x^2+y^2+2x-3=0(√是根号)√x^2+y^2/√(x-3)^2+y^2=1/2 如何化简成曲线方程:x^2+y^2+2x-3=0
√(x^2+y^2)/√[(x-3)^2+y^2]=1/2,
——》2√(x^2+y^2)=√[(x-3)^2+y^2],(两边平方)
——》4(x^2+y^2)=(x-3)^2+y^2,
——》3x^2+3y^2+6x-9=0,
——》x^2+y^2+2x-3=0.
先化简 再求值 (2x-y)(y+x)-(x-2y)(2y+x)-(-3y+x)^2其(√x+1)+y^2+4=-4y
x(x-y)2-(y-x)3
[2/3x-2/x+y(x+y/3x-x-y)]/x-y/x
化简:{2/3x-2/(x+y)[(x+y)/3x-x-y]}/(x+y)/x
计算2/3x-2/x+y(x+y/3x-x-y)/x-y/x
化简3x-2/(x+y)[(x+y)/3x-x-y]÷(x-y)/x
y^2-2(√x+1/√x)y+3
若x>0,y>0,且√x(√x+√y)=3√y(√x+5√y),求2x+2√x*√y+3y/x-√x*√y+y
x-y/x-x+y/y-(x+y)(x-y)/y² y/x=2
计算:x+2y/x-y+2x/y-x-3y/x-y
化简:(x-3y)(x+y)-(x-2y)(x+2y)-(x-y)平方
[(3x+y)(x-y)-(2x+3y)(x-y)]*(x-y)
已知√(y/x)+√(x/y)=3√2/2,那么y/x+x/y的值为
若x,y∈{-√3,-1,1,2},则(x,y)∈{(x,y)|x^2+y^2
√x+y-3+/xy+x+y-2/=0,求x÷y+y÷x的值.
³√x+y=3,√x-y=2 求x,y的平方根
|2x+y+1|+√2y+3x=0则x.y=
|x-2y|+√3x-4y =0求x y值